2019
DOI: 10.3389/fpls.2018.01987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temporal Heterogeneity of Water Supply and Spatial Heterogeneity of Soil Nutrients on the Growth and Intraspecific Competition of Bolboschoenus yagara Depend on Plant Density

Abstract: Clonal plants may face various types of resource heterogeneity in their natural habitats; as such, spatial or temporal resource heterogeneity can affect the growth of clonal plants. Clonal plants can concentrate their organs in a smaller area where resources are high would cause heterogeneity to increase competition between plants. Most studies on resource heterogeneity have investigated the response of plants under a single density or by manipulating a single resource. Few studies have tested the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Plants in natural habitats often experience heterogeneity in the spatial and temporal distribution of soil nutrients [21,46]. Wetland plants, especially emergent macrophytes, are sensitive to the distribution of soil pollutants and nutrients during their growth process [7,45]. In addition, clonal plants often exhibit more sensitive reactions than non-clonal plants; for example, the ramets of clonal plants interconnected by spacers (rhizomes, stolons, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Plants in natural habitats often experience heterogeneity in the spatial and temporal distribution of soil nutrients [21,46]. Wetland plants, especially emergent macrophytes, are sensitive to the distribution of soil pollutants and nutrients during their growth process [7,45]. In addition, clonal plants often exhibit more sensitive reactions than non-clonal plants; for example, the ramets of clonal plants interconnected by spacers (rhizomes, stolons, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…These may be due to water shortage and predominant high temperature in Southern Alberta this year (Tubiello et al, 2007). The results of Yu et al (2019) on Bolboschoenus plants also supported some plant varieties accumulate greater biomass and yield under heterogeneous conditions than under homogeneous conditions, given the same level of available concentration of nutrients. Both fallow and unfallow soils influenced heterogeneous soil nutrients availability in different area (locations) under the same rate of fertilizer application (Hutchings & Wijesinghe, 2008;García-Palacios et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
“…Water supply is the one of the requirement for plant growth. It was confirmed that a stable water supply (homogeneity of water supply) can promote plant root systems to absorb water more efficiently and thus grow larger plants (Novoplansky and Goldberg, 2001;Hagiwara et al, 2012, Yu et al 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have showed that the effects of LU/LC on ecosystem services differ temporally and spatially [22,[30][31][32][33]. Water supply services are susceptible since they are exposed to severe natural stresses related to interactions among biophysical factors, which considerably increase their heterogeneity from a temporal and spatial perspective [34,35]. Several relatively static influences (soil, topography, and geology) and dynamic influences (land use, land management, and climate) interact to control water access and how it will be distributed to competing users [23].…”
Section: Introductionmentioning
confidence: 99%